Diskursus Zakat Produktif Syekh Muhammad Arsyad Al-Banjari - Fathullah Munadi; Muhammad Nur Effendi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2021)
Abstract: Sheikh Arsyad's conception of productive zakat was deduced from Kitāb al-Zakāt in Sabilal. This conception became a hot discourse when several academics claimed that this conception was a new ijtihad from Sheikh Arsyad. The claim criticized by Muslich Shabir on research using intertextual analysis, 2004.This paper is written as a review of the discourse that occurs around Sheikh Arsyad's productive zakat, especially regarding differences of opinion on the position of the concept of productive zakat in ijtihad. The above discourse is then withdrawn to determine the position of this productive zakat concept in the local discourse of the archipelago.From this discussion it can be concluded that Syekh Arsyad in this theme is in line with his predecessor, this shows that he is consistently guided by the basis of law-making which is more dominant and applies universally. On the other hand, he can also be considered as the pioneer of the inclusion of the discourse of productive zakat in fiqh works which use the Malay language. Abstrak: Konsepsi zakat produktif Syekh Arsyad disimpulkan dari Kitāb al-Zakāt dalam Sabilal. Konsepsi ini menjadi wacana yang hangat ketika beberapa akademisi yang melakukan klaim bahwa konsepsi ini merupakan ijtihad baru dari Syekh Arsyad. Pernyataan ini kemudian mendapat kritik dari Muslich Shabir melalui penelitian menggunakan analisis intertekstual, tahun 2004.Tulisan ini ditulis sebagai review terhadap diskursus yang terjadi sekitar zakat produktif Syekh Arsyad, terutama terhadap perbedaan pendapat dalam posisi konsep zakat produktif dalam ijtihad.  Dari wacana di atas dapat ditarik kesimpulan tentang posisi konsep zakat produktif ini dalam wacana lokal nusantara.Dari pembahasan ini dapat disimpulkan bahwa Syekh Arsyad dalam tema ini sejalan dengan tokoh pendahulunya, ini menunjukkan bahwa ia konsisten berpedoman kepada dasar pengambilan hukum yang lebih dominan dan berlaku secara universal. Di lain pihak ia juga dapat dianggap sebagai pelopor masuknya wacana zakat produktif ini dalam karya fiqh yang menggunakan bahasa Melayu.